(untitled) (World Science, 2020)
The architectural and historical environment concentrates and integrates the main elements of the city cultural values, having a high uniqueness rating. It structures and brings unity and identity to the city, while constantly adapting to changing social demands. The modern stage of the architectural and historical environment development is that the atmosphere of the formed space becomes anachronistic, while its content, perception and experience of use are changing. There is a need for the successive development of historical values and the acquisition of new environmental qualities. The architectural and historical environment faces new challenges and tasks.